2020
DOI: 10.1002/slct.202003389
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bismuth Catalysts for the Methanolysis of End‐of‐Life Poly(lactide)

Abstract: The chemical recycling of poly(lactide) (PLA) was investigated especially the depolymerization for generating useful monomers/polymer precursors. In more detail, applying catalytic amounts of bismuth compounds PLA was converted to methyl lactate using methanol as depolymerization reagent. An excellent performance was observed for bismuth subsalicylate with turnover frequencies of up to 13,800 h À 1 using microwave heating. Moreover, the usefulness of the bismuth subsalicylate catalyst was demonstrated in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…For both bismuth subsalicylate and Zn(OAc) 2 , high Me‐LA yield (>99 %) was retained irrespective of PLA source. [ 138 , 139 ] Conversely, Me‐LA yield was found to vary more significantly for the alkali halide and Sn(Oct) 2 systems, observing moderate to high yields (43–128 %). Note yields greater than 100 % were observed in instances when the starting material was assumed to be 100 % PLA but contained a substantial number of additives by mass (e. g., black sushi box).…”
Section: Chemical Recycling Of Poly(lactic Acid)mentioning
confidence: 99%
See 2 more Smart Citations
“…For both bismuth subsalicylate and Zn(OAc) 2 , high Me‐LA yield (>99 %) was retained irrespective of PLA source. [ 138 , 139 ] Conversely, Me‐LA yield was found to vary more significantly for the alkali halide and Sn(Oct) 2 systems, observing moderate to high yields (43–128 %). Note yields greater than 100 % were observed in instances when the starting material was assumed to be 100 % PLA but contained a substantial number of additives by mass (e. g., black sushi box).…”
Section: Chemical Recycling Of Poly(lactic Acid)mentioning
confidence: 99%
“…This is particularly impressive given catalyst recovery is often a limiting industrial feature of homogeneous catalysis. Recently, Enthaler and co‐workers[ 136 , 137 , 138 , 139 ] have extensively reported the use of simple metal salts for PLA alcoholysis under microwave irradiation. Commercially available alkali halide salts of the general formula MX, such as KF, LiCl and KBr, were found to be potent catalysts for PLA ( M n =43600–150400 g mol −1 ) methanolysis between 140–160 °C.…”
Section: Chemical Recycling Of Poly(lactic Acid)mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Furthermore, Enthaler and coworkers have recently utilised F for the depolymerisation and chemical recycling of end of life PLA materials. 19 However, the Bi initiator is insoluble and the nature of the active species is not known but is likely to be a polynuclear species based on crystallographic studies of the parent subsalicylate; importantly, the insolubility renders catalytic activity dependent on particle size. 20 Bi{N(SiMe 3 ) 2 } 3 has been investigated by Visseaux and coworkers as a simple, soluble initiator (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be mentioned that quite recently a study about methanolytic degradation (and recycling) of used polylactide articles catalyzed by various Bi(III) salts was published 33 . There, it was found that BiSub was the most effective transesterification catalyst of all Bi(III) salts used in that study.…”
Section: Resultsmentioning
confidence: 86%